Istikhdamu al-Tasykiil Li Tarqiyah Maharah al-Qiraah bi Madrasah Dar al-Salafi - Hindun, Hindun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The reading skill is one of the four language skills and is a key to learning the new language in terms of books, magazines, and the like. Reading Arabic texts is not easy. As for mastering the skill of reading, it means having the ability to understand what is read in a correct and good way. For beginners in learning the Arabic language, reading textbooks and homework without movements is difficult for them because they do not possess and do not know the science of grammar, which is not like reading the Holy Quran. With the passage of time, technology is increasing, and it is known that the role of the media is very important in learning the Arabic language. Experts have provided applications or websites to facilitate learning the Arabic language, including